An Examination of Cultural Competitiveness and Order Fulfillment Cycle Time within Supply Chains - Hult, G. Tomas M.; Ketchen, David J.; Nichols, Ernest L. (Academy of Management Journal, 2002)
Supply chains are increasingly important, yet little is known about the determinants of their success and failure. Drawing on the resource-based view and research on ?adhocracy,? in this study we examined the effects of cultural competitiveness within supply chains on order fulfillment cycle time. The results indicate that entrepreneur-ship, innovativeness, and learning function as first-order indicators of a higher-order latent construct we label ?cultural competitiveness? that, in turn, has a positive effect on cycle time reduction.